2004
DOI: 10.1086/379794
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Visual Signal Design and Detectability between Allopatric Populations ofAnolisLizards

Abstract: We tested the prediction of the sensory drive hypothesis using four allopatric populations of the lizard Anolis cristatellus from two distinct environments (i.e., mesic and xeric conditions). For each population, we measured habitat light characteristics and quantified signal design by measuring the spectral and total reflectance and transmittance of the dewlap. We used these data to calculate dewlap detectability using an empirically based model of signal detection probability. We found that populations from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
202
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(210 citation statements)
references
References 58 publications
8
202
0
Order By: Relevance
“…This may either stem from both trait and sensor being shaped by the same environment, or because they are in fact co-evolving (Boughman, 2002). Specific light environments of different habitats likely shape the signals used in communication and signal design has indeed been found to be associated with detectability (Leal and Fleishman, 2004). It is thus feasible that different environments exert selection pressure not only on genes that underlie the phenotypic characteristic itself (the signal), but also on genes that underlie the ability to observe the trait (the ability to perceive the signal).…”
Section: Discussionmentioning
confidence: 99%
“…This may either stem from both trait and sensor being shaped by the same environment, or because they are in fact co-evolving (Boughman, 2002). Specific light environments of different habitats likely shape the signals used in communication and signal design has indeed been found to be associated with detectability (Leal and Fleishman, 2004). It is thus feasible that different environments exert selection pressure not only on genes that underlie the phenotypic characteristic itself (the signal), but also on genes that underlie the ability to observe the trait (the ability to perceive the signal).…”
Section: Discussionmentioning
confidence: 99%
“…The environment affects signal transmission by adding noise and altering signal properties (Endler, 1992;Marten and Marler, 1977), whereas receiver characteristics dictate the structural correlates of conspicuousness (e.g. Leal and Fleishman, 2004), audibility (e.g. Klump et al, 1986) and localizability (Wood et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Barquero et al (2015) reported that different populations of Amphibolurus muricatus exhibited subtle variation in display structure and suggested habitat differences as a potential driving force. This is precisely the kind of habitat-dependent variation in signal structure often documented for other modalities (color: Leal and Fleishman, 2004;Ng et al, 2013;McLean et al, 2015;sounds: Ryan et al, 1990;Potvin and Parris, 2012), but has not been quantified in analogous detail for signals defined by motion. The methodology we propose here will facilitate the generation of such data.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, Peters and Evans (2003) employed the same methodology to compare velocity signatures from lizard signals and plant sequences in order to estimate the relative conspicuousness of each motor pattern in the lizard display. This led to a much better understanding of motion signal structure and opened the path to many studies on the influence of the environment on lizard signaling behavior (Leal and Fleishman, 2004;Ord et al, 2007Ord et al, , 2010Peters et al, 2007Peters et al, , 2008Ord and Stamps, 2008;Fleishman and Pallus, 2010).…”
Section: Introductionmentioning
confidence: 99%